Republic of Armenia : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report provides an assessment of the Observance of Standards and Codes on Fiscal Transparency Module for the Republic of Armenia. Armenia has made substantial progress in recent years to improve a number of aspects of fiscal transparency. It has achieved significant results, especially regarding the legal framework and reporting. This progress will be furthered when the draft laws currently under consideration by the authorities, especially the treasury law, the law on state debt, and the disclosure requirements on high-ranking officials' property and income, are effectively implemented.